Gold mineralization of the Median Massif, Kamchatka (Kamchatka Sredinnyi Massif) - V. A. Stepanov; V. E. Kungurova; I. A. Koidan (Известия высших учебных заведений: Геология и разведка)
The gold mineralization of the Kamchatka median massif has been analyzed. It has been shown that within its lim-its, the ore mineralization of low-sulphide gold-quartz and gold-sulfide-quartz formations and also placers, formed on the base of this mineralization are widely developed. A significant role is played also by the ore occurrences of the gold-copper-molybdenum-porphyry formation, prospecting for the discovery of large deposits with complex ores. Gold in the form of associated component is also presented in the ores of the Shanuch deposit and manifestations of the sulfide copper-nickel formation. Three stages of ore formation have been identified: late Cretaceous, Eocene and Miocene. In the late Cretaceous stage mineralization of gold-quartz and gold-sulfide-quartz formation was formed, in the Eocene — sulfide copper-nickel one, and in the Miocene — gold-copper-molybdenum-porphyry one. The pros-pects of gold mineralization of the median massif has been defined.